RUANG SAKRAL PERMUKIMAN TRADISIONAL MAMASA - Timbang, Gator; Luthfiah; Setiawan, Altim (JURNAL RUANG / ISSN : 2085-6962, 2019)
The problems raised in the research with the Mamasa community settlement locus focus on the issue of segregation of sacred and profane space as an effort to know and understand local wisdom in the field of architecture, especially the nature of space in the context of unique ethnic cultural and religious settlements as part of archipelago architecture who has the soul behind his physical performance. The purpose of this research is to find out and describe what the sacred space is in the context of the Mamasa ethnic settlement. This ethnic life is still integrated with Alu 'Todolo's teachings as an ancestral religion that implies religious rituals in various moments and activities are wrapped in the frame of their lives. Therefore, through qualitative methods with a post positivistic paradigm, it is hoped that this research can explore how the sacred space in its traditional settlements.